Floristic diversity and conservation strategies in cold desert of western Himalaya, India - Srivastava, Sunil Kumar (Botanica Orientalis: Journal of Plant Science, 2011)
The rich flora of cold desert constitutes an incredible store house of plant genetic resources that contribute not only to the livelihoods of enormous number of forest dwelling but also to the various pharmaceuticals industry. The plant wealth of Ladakh in Jammu and Kashmir, Lahaul-Spiti in Himachal Pradesh and Nelang valley in Uttarakhand falls in cold desert region of North-West Himalaya. The floristic documentation of this area represents ca 1405 species, 490 genera under 98 families of flowering plants. A large number of species growing in this area are of medicinal and economic value and used by local inhabitants for curing their ailments. Floristic analysis, brief account of physiography, vegetation types and adaptations in the plants for their survival, endemism, threatened taxa, medicinal and economic plants have been discussed along with the threats and conservation strategies. Key-words: Floristic; Diversity; Conservation; Cold Desert; India DOI: 10.3126/botor.v7i0.4369 Botanica Orientalis – Journal of Plant Science (2010) 7: 18-25